(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
The article deals with the theoretical aspects of the functioning of the symbol "soul" in a literary work on the example of Ukrainian writers such as T. Shevchenko, I. Franko, M. Rylskyi, V. Sоssure, L. Kostenko, D. Pavlichko. The ability of the soul to create a holistic discourse, which can act as a comparison, metonymy, to provoke a particular syntactic way, refine chronotope has been analyzed.